2019
DOI: 10.35808/ersj/1460
|View full text |Cite
|
Sign up to set email alerts
|

Price Formation around Dividend Announcement Date: Empirical Evidence in Indonesian Stock Exchange

Abstract: Purpose: This research aims to prove that there is a change in abnormal return around the dividend announcement date. Based on differences in the interests of rational and irrational investors related to the dividend announcement and subsequent event, the authors propose two research questions: first, whether there is an abnormal return around the dividend announcement date; second, whether price changes around that event. Design/Methodology/Approach: The time span of the study was five days before and five da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
2
1
Order By: Relevance
“…Therefore, Indonesian Stock Exchange provides a sluggish response toward the event. This result is in line with the research by Mujib and Candraningrat ( 2021 ) and Frensidy et al ( 2019 ) who have also found insignificant negative abnormal returns toward the COVID-19 pandemic, as well as Anwar et al ( 2017 ) who discovered that during a recession period of 2003–2013, the returns of the stock decreased significantly compared to the normal condition.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, Indonesian Stock Exchange provides a sluggish response toward the event. This result is in line with the research by Mujib and Candraningrat ( 2021 ) and Frensidy et al ( 2019 ) who have also found insignificant negative abnormal returns toward the COVID-19 pandemic, as well as Anwar et al ( 2017 ) who discovered that during a recession period of 2003–2013, the returns of the stock decreased significantly compared to the normal condition.…”
Section: Resultssupporting
confidence: 90%
“…The result obtained is not aligned with the study from Frensidy et al ( 2019 ) who has analyzed the dividend effect in Indonesia Stock Exchange from 2007 to 2012 and discovered a significant abnormal return around the dividend announcement date. Frensidy et al ( 2019 ) has also mentioned that significant abnormal returns indicate an active response from the market to gain returns from the event. Thus, it confirms that the stock market manifests weak and delayed response toward the event.…”
Section: Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…Consequently, the shareholders might as well study the company's condition more thoroughly to make investment decisions. Frensidy et al (2019) have found a significant abnormal return around the dividend announcement date as guided by the power of information attached into dividend announcement. This phenomenon lies on the foundation of two schools of thought namely dividend relevance and dividend irrelevance.…”
Section: Dividend Signaling Theorymentioning
confidence: 99%